IMPROVEMENTS IN THE DIAGNOSIS OF OBSTRUCTIVE SLEEP APNEA IN CHILDREN - Luminiţa Rãdulescu; Cristian Mârțu; Dan Mârțu; Horia Chiriac; Sorin Corodeanu (Romanian Society of Oral Rehabilitation, 2016)
Obstructive sleep apnea in children is due to adeno-tonsillar hypertrophy, in the majority of cases - a common condition in children that can be cured by the ENT surgeon by a relatively safe surgery. The final diagnosis of Obstructive sleep apnea is possible with polysomnography. This test is difficult to be performed in small children due to the contact sensors that are displaced during the agitated sleep of a child with sleep apnea. We propose a quasi noncontact sensor to be used to record the respiratory movements of children during sleep. The preliminary tests show that the method might be applicable in the clinical settings.